Correlation analysis between dance experience and smoothness of dance movement by using three jerk-based quantitative methods - Park, Y. S. (Korean Journal of Sport Biomechanics, 2016)
Objective: The aim of this study is to investigate the association between dance experience and smoothness of hand trajectory during dance by using three jerk-based quantitative methods (integrated squared jerk, mean squared jerk, and dimensionless jerk). Methods: Eleven Korean traditional dancers whose experience of dancing ranged from 5 years to 20 years participated in this study. Dancers performed the Taeguksun motion in Korea traditional dance. Six infrared cameras were used to capture the movement of the hands of the dancers. The smoothness of hand movement was calculated using three jerk-based methods. Results: With regard to the smoothness of the right hand, dance experience was significantly correlated with dimensionless jerk (r=0.656, p=0.028), while dance experience was not significantly correlated with integrated squared jerk (r=0.581, p=0.552) and mean squared jerk. With regard to the smoothness of the left hand, there was no correlation between dance experience and any of the three jerk values. Conclusion: Our results showed that individuals with more dance experience performed the task more smoothly. This study suggests that dimensionless jerk should be used as a predictor for smoothness in dance movement. Thus, our results support the idea that smoothness is an aspect of movement quantity distinct from speed and distance.